2014
DOI: 10.1007/s12603-014-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intake of nuts in relation to cognitive function in older women

Abstract: Objective Nuts contain nutrients that may benefit brain health; thus, we examined long-term intake of nuts in relation to cognition in older women. Design Population-based prospective cohort study. Setting Academic research using data from the Nurses’ Health Study. Participants Nut intake was assessed in a food-frequency questionnaire beginning in1980, and approximately every four years thereafter. Between 1995–2001, 16,010 women age 70 or older (mean age = 74 years) without a history of stroke were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 26 publications
6
61
0
Order By: Relevance
“…Also, an observational study showed a 47% reduction in all-cause mortality and 36% reduction in cancer deaths in people who ate nuts ≥8 times/month, compared to those who never ate nuts during a median follow-up of 4.3 years (36). Additionally, consumption of nuts was also shown to be protective against cognitive decline in elderly people (37), or even to improve cognitive function (7). …”
Section: Discussionmentioning
confidence: 99%
“…Also, an observational study showed a 47% reduction in all-cause mortality and 36% reduction in cancer deaths in people who ate nuts ≥8 times/month, compared to those who never ate nuts during a median follow-up of 4.3 years (36). Additionally, consumption of nuts was also shown to be protective against cognitive decline in elderly people (37), or even to improve cognitive function (7). …”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study of NHANES 1988–1994 and 1999–2002 data showed that adults, aged 20–59 years and 60 years and older and who had consumed nuts, had significantly higher scores on story recall and digit–symbol substitution, faster reaction time, faster symbol–digit substitution time, and greater single‐digit learning scores compared with nonconsumers . Results from the Nurses’ Health Study, including 15,467 women, also showed protective effects of nut intake on cognitive function; women consuming at least five servings of nuts/week had significantly higher scores on global cognitive function, although not significantly associated with rates of cognitive decline over time . A trial examining intake of Brazil nuts among older adults with mild cognitive impairment found that the treatment group showed significant improvement in verbal fluency and constructional praxis, compared to controls …”
Section: Nuts and Seedsmentioning
confidence: 99%
“…Consequently, as derived from epidemiologic studies, a promising hypothesis in recent years has been that antioxidant-rich foods, such as fruit, vegetables, and particularly seeds and berries (Nooyens et al, 2011; Valls-Pedret et al, 2012; Ros and Hu, 2013; Barbour et al, 2014; O’Brien et al, 2014), and plant-based dietary patterns, especially the Mediterranean diet and the DASH (Dietary Approaches to Stop Hypertension) dietary pattern (Otaegui-Arrazola et al, 2014; Tangney et al, 2014) may protect from cognitive decline and AD. Nutrients such as n-3 polyunsaturated fatty acids (n-3 PUFA) and antioxidants, namely polyphenols, carotenoids and vitamins C and E, may have a role in preventing both cognitive impairment (Macready et al, 2009; Dangour et al, 2012; Valls-Pedret et al, 2012; Devore et al, 2013; Barnes et al, 2014; Otaegui-Arrazola et al, 2014) and macular degeneration (Age-Related Eye Disease Study Research Group, 2001; Parisi et al, 2008; Tan et al, 2009; Majumdar and Srirangam, 2010; Merle et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nuts in general and walnuts in particular have a rich matrix of these bioactive components and through additive effects have the potential to beneficially impact neuronal function in the brain and the retina (Poulose et al, 2014). Prospective studies have provided support for the association between nut consumption and improved cognitive performance (Valls-Pedret et al, 2012; O’Brien et al, 2014) and lower incidence of AMD (Tan et al, 2009; Amirul Islam et al, 2014). Among the different tree nuts, walnuts contain n-3 PUFA, specifically α-linolenic acid (ALA; C18:3n-3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation